Reaction of 2,4-dinitrochlorobenzene with aromatic amines in toluene: Effect of nucleophile structure - Alvaro, C.E.S. (2000)
The kinetics of the reaction of 2,4-dinitrochlorobenzene (DNClB) with aniline and substituted anilines such as p-anisidine, p-toluidine and N-methylaniline have been studied in toluene. Except for N-methylaniline the reactions have shown a third order in amine rate dependence which is consistent with aggregates of the amine acting as the nucleophile. On the other hand, the reaction of DNClB with N-methylaniline under the same conditions shows a linear dependence of the second order rate coefficient, kA, vs [amine], which is consistent with the previous mechanism.